Impaired efferocytosis and neutrophil extracellular trap clearance by macrophages in ARDS. Issue 2 (2nd August 2018) - Grégoire, Murielle; Uhel, Fabrice; Lesouhaitier, Mathieu; Gacouin, Arnaud; Guirriec, Marion; Mourcin, Frederic; Dumontet, Erwan; Chalin, Arnaud; Samson, Michel; Berthelot, Laure-Line; Tissot, Adrien; Kerjouan, Mallorie; et al.
Exaggerated release of neutrophil extracellular traps (NETs) along with decreased NET clearance and inability to remove apoptotic cells (efferocytosis) may contribute to sustained inflammation in acute respiratory distress syndrome (ARDS). Recent studies in experimental models of ARDS have revealed the crosstalk between AMP-activated protein kinase (AMPK) and high-mobility group box 1 (HMGB1), which may contribute to effectiveness of efferocytosis, thereby reducing inflammation and ARDS severity. We investigated neutrophil and NET clearance by macrophages from control and ARDS patients and examined how bronchoalveolar lavage (BAL) fluid from control and ARDS patients could affect NET formation and efferocytosis. Metformin (an AMPK activator) and neutralising antibody against HMGB1 were applied to improve efferocytosis and NET clearance. Neutrophils from ARDS patients showed significantly reduced apoptosis. Conversely, NET formation was significantly enhanced in ARDS patients. Exposure of neutrophils to ARDS BAL fluid promoted NET production, while control BAL fluid had no effect. Macrophage engulfment of NETs and apoptotic neutrophils was diminished in ARDS patients. Notably, activation of AMPK in macrophages or neutralisation of HMGB1 in BAL fluid improved efferocytosis and NET clearance. In conclusion, restoration of AMPK activity with metformin or specific neutralisation of HMGB1 in BAL fluid represent promising therapeutic strategies to decrease sustained lung inflammation during ARDS. Restoration of AMPK activation and specific inhibition of HMGB1 could reduce lung inflammation during human ARDS http://ow.ly/bxCj30ktyiZ